Minimally Invasive Management of Dental Fluorosis with a Combination Technique: A Case Report - Daryakenari, Ghazaleh; Sanjari, Khashayar; Ebrahimizadeh, Hosna (Journal of Dental School, 2020)
Objectives Dental fluorosis is a condition characterized by hypomineralization of tooth structure. It manifests as bilateral white opaque discolorations. Patients with these kinds of staining and discoloration often present to dental offices in young ages, seeking esthetic solutions. Color, shape and structural alterations in the anterior teeth could lead to significant esthetic complications for young patients. There are many cosmetic options to correct the unpleasant appearance of the anterior teeth. Dental bleaching is a conservative treatment for stained or dark-colored teeth. Micro-abrasion and removal of the outer layer of the tooth is another effective and successful method to treat fluorosis. Resin infiltration can also significantly change the esthetic appearance of such teeth. Case Micro-abrasion followed by tooth bleaching and application of resin infiltrate was used in this study as a minimally invasive and inexpensive approach to treat discolored teeth due to dental fluorosis. Conclusion To treat discolored teeth affected by dental fluorosis, a minimally invasive and inexpensive approach would be micro-abrasion followed by tooth bleaching and resin infiltration. This approach obviates the need for more invasive techniques such as veneers and crowns while it meets the esthetic demands of patients.